Faktor-faktor yang Memengaruhi Motivasi Petani dalam Usahatani Bawang Merah di Tanggedu Kecamatan Kanatang Kabupaten Sumba Timur - Atandima, Marlin Day; Retang, Elfis Umbu Katongu (Universitas Galuh, 2024)
This research aims to analyze the level of motivation and the influence of internal and external factors on the motivation of red onion farmers in Tanggedu, Kanatang District, East Sumba Regency. Determining the sample size in this study used saturated sampling or census, where all members of the population were used as samples. The sample used in this research was 69 respondents who were red onion farmers in Tanggedu. Analysis of the level of farmer motivation was carried out using a Likert scale, then to determine the influence of internal and external factors on farmer motivation an analysis was carried out using the multiple linear regression function model equation. The results of the analysis illustrate that the motivation of farmers in cultivating red onion in Tanggedu is in the very high category. The results of the analysis of the influence of internal factors on motivation explain that partially income, number of family dependents, and farming experience have a significant influence on farmer motivation, while age and education do not have a significant influence. Together, age, education, income, number of family dependents and farming experience have a significant effect on farmers' motivation in cultivating red onion farming in Tanggedu. The results of the analysis of the influence of external factors on motivation explain that partially the market, farming risks, extension and facilities have a significant influence on farmer motivation, while capital institutions do not have a significant influence. Together the market, farming risks, extension, facilities and capital institutions have a significant influence on farmers' motivation in cultivating red onion farming in Tanggedu.